2019
DOI: 10.3126/jkahs.v2i1.24390
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Index of Conciousness (Ioc2) Monitoring on Remifentanil Dosage During Desflurane Anesthsia: A Randomized Trial

Abstract: Background: Our study investigated the effects of IOC2 index monitoring on remifentanil dosage during desflurane anesthesia. The objective of this study was to compare the intra-operative events and recovery characteristics between remifentanil adjusted by IOC2 monitoring guidelines versus remifentanil adjusted by clinical experience according to fluctuation in blood pressure and heart rate during desflurane anesthesia. Methods: Total of 50 consecutive patients of American Society of Anesthesiologists (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Wang and co-worker in a randomized clinical trial in 60 women scheduled for lower abdominal surgery under general anesthesia or spinal anesthesia concluded that postoperative pain after lower abdominal surgery can be significantly decreased if the surgery is performed under spinal anesthesia with 3 ml of hyperbaric 0.5% bupivacaine. 4 The postoperative recovery of the patients was normal, it is described that spinal anesthesia is associated with lower frequency of serious postoperative morbidities and an improved outcome when compared to general anesthesia. 5,6 Spinal anaesthesia is much safer for patients of respiratory diseases as Scott et al showed, pulmonary complications were more common in patients who underwent GA compared with regional anaesthesia.…”
Section: Discussionmentioning
confidence: 94%
“…Wang and co-worker in a randomized clinical trial in 60 women scheduled for lower abdominal surgery under general anesthesia or spinal anesthesia concluded that postoperative pain after lower abdominal surgery can be significantly decreased if the surgery is performed under spinal anesthesia with 3 ml of hyperbaric 0.5% bupivacaine. 4 The postoperative recovery of the patients was normal, it is described that spinal anesthesia is associated with lower frequency of serious postoperative morbidities and an improved outcome when compared to general anesthesia. 5,6 Spinal anaesthesia is much safer for patients of respiratory diseases as Scott et al showed, pulmonary complications were more common in patients who underwent GA compared with regional anaesthesia.…”
Section: Discussionmentioning
confidence: 94%